Current situation and expectation of emergency medicine education for 8-year Doctor of Medicine degree program in China. Issue 6 (November 2022) - Ge, Zengzheng; Feng, Shi; Liu, Xiangning; Guo, Shigong; Gao, Yanxia; Lu, Xin; Yu, Shiyuan; Zhao, Lina; Shi, Di; Liu, Jihai; Zhu, Huadong; Li, Yi
Background: Appropriate lessons and formalized training concerning emergency medicine is becoming increasingly important in undergraduate medical education. There is an urgent need to evaluate undergraduate emergency medicine education of students enrolled on the 8-year Doctor of Medicine degree programs nationwide in China with the aim that the data extracted could ultimately be used to help develop a standardized emergency medicine curriculum in China. Objectives: The aim of the study is to accurately describe emergency medicine education of 8-year Doctor of Medicine program in China, including emergency medicine classes, clinical practice in emergency medicine department, and expectations toward emergency medicine education. Methods: An online questionnaire was distributed to all the medical students of 8-year Doctor of Medicine program who have attended emergency medicine education in 14 medical schools in China. Participation in the survey was voluntary and anonymized. Results: In total, 529 valid responses were collected. There was a clear difference between students with a career aspiration in emergency medicine and those without. Comparing to countries that have an established emergency medicine curriculum, shortage of classroom hours and clinical practice time is a major cause of unsatisfactory educational outcomes in China. A detailed uniform emergency medicine curriculum that outlines exact requirements for medical students is required as well. Conclusion: A consolidated syllabus and curriculum should be compiled by all the medical schools with the 8-year integrated Doctor of Medicine degree program in China. The specific diseases and skills that should be covered in emergency medical education remain up to debate.